Strategi Pembelajaran Pendidikan Islam dalam Meningkatkan Literasi Keagamaan di MAN 2 Payakumbuh - Dea Two Onel Putri; Syarifah Rahmatul ‘Aini; Yugo Twoana Putra; Gusmaneli Gusmaneli (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
The article is entitled "Islamic education learning strategies in increasing religious literacy. This article was written because students still lack interest in reading Islamic education books. This article explores what kind of application of Islamic education learning strategies in increasing religious literacy by teachers of Islamic education subjects such as moral beliefs at MAN 2 Payakumbuh. The aim is to find out what obstacles there are in its implementation. This type of research uses a qualitative approach to describe the implementation of Islamic education learning strategies to increase religious literacy at MAN 2 Payakumbuh. We obtained data through interviews with class XI Aqidah Akhlak teachers, and interviews with class XI students as well as observations. This research obtained the results that the implementation of Islamic education learning strategies implemented by schools and implemented by teachers was not satisfactory and still had many shortcomings. There were 5 strategies implemented, namely: visiting the library, asking students to read for 20 minutes before learning started, making wall magazines, organizing a literacy corner for each class, organizing competitions related to literacy. Even though all strategies have been implemented, there are still gaps. The obstacles to students' lack of interest in reading textbooks, especially Islamic education books, are students' lack of interest in reading textbooks and students' lack of awareness of the importance of reading textbooks, external factors, namely the environment, from friends, from the family environment and school facilities that are rarely used.